Lightning Discharge Test of 10kV Distribution Network Insulation Cross Arm and Comprehensive Evaluation of Lightning Protection Effect - Huang, Weixiang; Lin, Xiuqing; Chen, Shaonan; Xia, Xiaofei; Feng, Bo; Chen, Qianyi; Li, Shan (2023 IEEE International Conference on Power Science and Technology (ICPST), 2023)
10kV distribution lines have low lightning withstand level and are easily affected by direct lightning or induced lightning, leading to insulator flashover or even tripping. In order to study the influence of insulated cross arm on the lightning withstand level of 10kV overhead distribution line combined with the actual situation, this paper first built a 10kV distribution line model, carried out lightning impact comparison test of insulated cross arm and iron cross arm, and obtained the lightning impact insulation strength of tower U50% under different cross arm types. Then, the numerical calculation method of lightning induced overvoltage of 10 kV overhead lines is proposed, and the self-defined lightning induced overvoltage calculation model is established by using MODELS language. Combined with the actual situation of 10kV power supply line of an oil transmission station in southern mountainous area, a co-simulation model of direct lightning strike and induced lightning overvoltage of 10kV distribution line was established by using ATP-EMTP, and the improvement effect of insulation cross arm on lightning resistance level was quantitatively analyzed. Finally, the effect of the device to improve the level of mine resistance is verified by the actual operation. The results show that replacing the iron cross arm of the cement tower with the composite insulating cross arm can significantly improve the lightning impulse insulation strength of the tower by U50%, which has the most significant effect on improving the lightning withstand level of the induced lightning of the line, followed by the lightning withstand level of the top of the lightning rod tower, and the lightning withstand level of the lightning stroke line has little improvement. The research results can provide reference for lightning protection design and transformation of distribution lines.